2008
DOI: 10.1089/jop.2007.0132
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Pharmacokinetics of a Single Dose of Bromfenac Sodium Ophthalmic Solution 0.1% in Human Aqueous Humor

Abstract: Pharmacokinetic modeling, based upon samples collected over 240 min after a single dose of bromfenac sodium ophthalmic solution 0.1% suggests that aqueous-humor concentrations remain at clinically effective levels (above its IC(50) value for COX-2) for over 12 h. Based upon this rationale, these results supported clinical trials that demonstrated the efficacy of twice-daily dosing of bromfenac sodium ophthalmic solution 0.1% to manage patients with postoperative ocular pain and inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 16 publications
1
17
1
Order By: Relevance
“…Also, in the placebo group, 21.6% (37/171) of the subjects discontinued the test agent due to lack of efficacy compared with only 3.1% (11/356) in the bromfenac group ( P <0.0001) (Table 2). Similar results were seen in the bromfenac 0.09% once-daily study,33 where early discontinuations from treatment occurred less frequently in the bromfenac group compared with the placebo group. Of the subjects in the placebo group, 16.2% (45/278) discontinued the test agent due to the occurrence of an AE compared with only 5.2% (29/559) in the bromfenac group ( P <0.0001).…”
Section: Bromfenac Compliance and Adherencesupporting
confidence: 78%
“…Also, in the placebo group, 21.6% (37/171) of the subjects discontinued the test agent due to lack of efficacy compared with only 3.1% (11/356) in the bromfenac group ( P <0.0001) (Table 2). Similar results were seen in the bromfenac 0.09% once-daily study,33 where early discontinuations from treatment occurred less frequently in the bromfenac group compared with the placebo group. Of the subjects in the placebo group, 16.2% (45/278) discontinued the test agent due to the occurrence of an AE compared with only 5.2% (29/559) in the bromfenac group ( P <0.0001).…”
Section: Bromfenac Compliance and Adherencesupporting
confidence: 78%
“…Although bromfenac has very good intraocular penetration into the aqueous humor in human [19], detailed pharmacokinetics for retinochoroidal tissue has not been determined. In rabbits, Baklayan et al have reported on the pharmacokinetic profiles of ocular tissues by using topical radiolabeled bromfenac [20], however, the relationship of the pharmacokinetics and efficacy in the target tissues has not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…In oral form, bromfenac has been shown to have superior potency when compared with other NSAIDs, with no systemic side effects 30,31. In its topical form, bromfenac has been shown to have enhanced intraocular penetration and distribution in the cornea, iris, ciliary body, retina, and choroids, along with a longer duration of action that may last for up to 24 hours at these sites 8,23,32–34. Bromfenac has been cited as being more selective toward COX-2, with ketorolac being more selective towards COX-1 35–37.…”
Section: Discussionmentioning
confidence: 99%